2014
DOI: 10.1097/md.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Patients Understand Written Instructions?

Abstract: The aim of this study was to assess health literacy (word recognition and comprehension) in patients at a rural rheumatology practice and to compare this to health literacy levels in patients from an urban rheumatology practice.Inclusion criteria for this cross-sectional study were as follows: ≥18-year-old patients at a rural rheumatology practice (Mid-North Coast Arthritis Clinic, Coffs Harbour, Australia) and an urban Sydney rheumatology practice (Combined Rheumatology Practice, Kogarah, Australia). Exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
0
17
2
Order By: Relevance
“…The medical literature is inconsistent concerning the observation that health literacy is better in urban populations [14, 15]. In the present analysis a better recognition of the correct definition was also not evident among participants from more populated areas; however, answer patterns differed between the federal states.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The medical literature is inconsistent concerning the observation that health literacy is better in urban populations [14, 15]. In the present analysis a better recognition of the correct definition was also not evident among participants from more populated areas; however, answer patterns differed between the federal states.…”
Section: Discussioncontrasting
confidence: 77%
“…Although women have been seen to have better medical knowledge and higher health awareness than men [ 13 ], the ability of both men and women in our study to identify the correct wording for “complication” was almost identical. The medical literature is inconsistent concerning the observation that health literacy is better in urban populations [ 14 , 15 ]. In the present analysis a better recognition of the correct definition was also not evident among participants from more populated areas; however, answer patterns differed between the federal states.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were likely to represent a highly engaged subset of the PH population. While the survey was offered in multiple formats (paper and electronic), the use of online survey advertising and dissemination may have favoured those with internet access, often a more literate population, 30 and those actively engaged with PH groups. Indeed, 67% of the present cohort reported an affiliation with at least one consumer support group, and levels of education in the present cohort appeared higher than the Australia population average.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In the UK, just under one in six adults has the literacy of an 11-year-old 26. A study of over 200 rural and urban Australian rheumatology patients found that 15% of patients had low health literacy and up to one-third of patients incorrectly followed dosing instructions for common rheumatology drugs 23. Ten per cent of patients with rheumatoid arthritis (RA) who attended an urban community-based Australian rheumatology practice had inadequate/marginal functional health literacy or a reading age at or below the US high school grade equivalent of seventh–eighth grade 27.…”
Section: Introductionmentioning
confidence: 99%